Animal models for understanding the mechanisms of malnutrition: a literature review - Shahzad, Muhammad; Ahmad, Habab Ali; Ghani, Mustajab; Al Nabhani, Ziad (Frontiers in Nutrition, 2025)
Malnutrition, encompassing undernutrition, micronutrient deficiencies, and overnutrition, remain a pervasive global health challenge. This underprivileged condition contributes significantly to worldwide morbidity and mortality and causes profound impairments in growth, development, immune function, and metabolic health. Understanding the underlying biological mechanisms is critical, and animal models are indispensable tools for dissecting these complex pathways and for evaluating potential nutritional interventions under controlled conditions that are infeasible in humans. This literature review comprehensively examines rodent models and explores other diverse animal models used to investigate malnutrition, ranging from invertebrates (e.g., Drosophila) and fish (zebrafish) to mammals (piglets and non-human primates). We highlight how each model has yielded mechanistic insights into malnutrition-induced pathophysiology, i.e., from altered metabolic signaling to immune dysfunction and critically evaluate their strengths and limitations in replicating the multifactorial nature of human malnutrition. Key considerations include the extent to which each model mimics human nutritional deficits or excesses, appropriate developmental stages, species-specific metabolic differences, and the influence of comorbid factors such as infection or gut microbiome alterations. We emphasize translational relevance by identifying where animal-derived findings align with clinical observations and where they diverge, underscoring the challenges in extrapolating preclinical results to human disease. Overall, this review provides a comprehensive resource to guide researchers in selecting appropriate animal models and interpreting their findings, with the ultimate goal of enhancing the translation of preclinical insights into improved strategies to address malnutrition.